PERHITUNGAN HARGA POKOK PRODUKSI DALAM PENETAPAN HARGA JUAL DENGAN METODE ACTIVITY BASED COSTING PADA UMKM DODONUT - Wahyuni, Fitri Permata; Astari, Chika Putri; Nuranjani, Dini; Larasati, Dian Ayu; Astuti, Asti; Zamanda, Davia; Situngkir, Tiar Lina (Faculty of economcs Universitas Singaperbangsa Karawang, 2024)
This study aims to determine production costs at Dodonut Shop using the Activity Based Costing (ABC) method. The ABC method was chosen because of its ability to provide more detailed cost information by identifying and allocating costs based on the activities performed. This research begins by identifying the main activities involved in the donut production process, such as raw material processing, frying, and packaging. Next, data was collected regarding the direct and indirect costs associated with each activity. The results of the analysis show that the ABC method provides a deeper understanding of production costs and helps Dodonut stores determine a more appropriate selling price and identify areas that require further efficiency. With the implementation of this method, Dodonut is expected to increase profitability and competitiveness in the market